CEO risk preferences and dividend policy decisions - Caliskan, Deren; Doukas, John A. (Journal of Corporate Finance, 2015)
This study examines whether risk aversion-inducing CEO compensation motivates managers to pay more dividends regardless of investor preferences. Using inside debt (i.e., pensions and deferred compensation) and the sensitivity of CEO equity compensation to stock price changes (i.e., high CEO delta), as proxies of CEO risk aversion, we document that inside debt induces CEOs to pay dividends while convex CEO compensation decreases dividend payout.